2014
DOI: 10.1007/s40593-014-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Augmented Reality Training for Motherboard Assembly

Abstract: We investigate the combination of Augmented Reality (AR) with Intelligent Tutoring Systems (ITS) to assist with training for manual assembly tasks. Our approach combines AR graphics with adaptive guidance from the ITS to provide a more effective learning experience. We have developed a modular software framework for intelligent AR training systems, and a prototype based on this framework that teaches novice users how to assemble a computer motherboard. An evaluation found that our intelligent AR system improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(125 citation statements)
references
References 31 publications
4
111
0
10
Order By: Relevance
“…First, many of the companies who are manufacturing industrial devices for AR are located in these countries (Market Reports Center, 2017). Moreover, several well-known research groups dedicated to exploring the use of AR for industrial applications are based in both Germany and the USA (Friedrich, 2002;Raczynski and Gussmann, 2004;Westerfield et al, 2015). In this respect, it is interesting to note that most of the studies carried out in Germany, the USA and China are technical papers, which suggests that these countries are particularly active in exploring new hardware/software AR features and confirms the relationships with the presence of research groups operating in two of these countries.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…First, many of the companies who are manufacturing industrial devices for AR are located in these countries (Market Reports Center, 2017). Moreover, several well-known research groups dedicated to exploring the use of AR for industrial applications are based in both Germany and the USA (Friedrich, 2002;Raczynski and Gussmann, 2004;Westerfield et al, 2015). In this respect, it is interesting to note that most of the studies carried out in Germany, the USA and China are technical papers, which suggests that these countries are particularly active in exploring new hardware/software AR features and confirms the relationships with the presence of research groups operating in two of these countries.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…The adaptive nature of the tool allows the user to enhance their learning experience by practicing concepts and viewing more direct examples of plays (See Figure 1). Additional work involving AR has shown clear benefits in assembly tasks, for instance in [4] was found that AR combined with ITS improves student performance and in [19] the AR trained group had fewer unsolved errors compare to the group that followed a filmed demonstration. We tested six of the most common concepts derived directly from official International Football Association Board "Laws of the Game 2016/2017" documentation [20].…”
Section: Related Workmentioning
confidence: 99%
“…The increasing availability of commercial, off-the-shelf technology, such as the Microsoft Hololens, makes AR a viable tool for a variety of training domains. This is particularly applicable in a domain such as sports, where not only visual cues are necessary, but spatial awareness and environmental cues are required for successful performance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Στο πλαίσιο των παραπάνω "πραγματικοτήτων", ενδιαφέρον παρουσιάζουν και οι δυνατότητες που παρέχουν οι Ευφυείς εικονικοί πράκτορες (IVAs), οι οποίοι με το διαδραστικό χαρακτήρα και τα ανθρώπινα χαρακτηριστικά και ιδιότητες που εμφανίζουν -π.χ. να επικοινωνούν με τους ανθρώπους ή με κάθε άλλο μέσο, χρησιμοποιώντας φυσικές ανθρώπινες λεπτομέρειες, όπως τις εκφράσεις του προσώπου, την ομιλία και την κίνηση -μπορούν να μειώσουν τα μειονεκτήματα της έλλειψης μαθησιακής επαφής (Westerfield, Mitrovic & Billinghurst, 2015• Kim et al, 2016. Επιπλέον, είναι σε θέση να αντιλαμβάνονται σε πραγματικό χρόνο, τη γνωστική λειτουργία και δράση που τους επιτρέπει να συμμετέχουν σε δυναμικά κοινωνικά περιβάλλοντα.…”
Section: η επαυξημένη πραγματικότητα στην εκπαίδευση και κατάρτισηunclassified